(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY To analyse medical end-of-life decision making among the oldest old (80+ years) in Switzerland, focusing not only on treatments withheld or withdrawn but also on those continued until death. METHODS This was a retrospective follow-up study of deaths registered in Switzerland between August 2013 and January 2014 using a standardised questionnaire completed by the attending physician. All individuals aged 65 years and older who did not die suddenly and completely unexpectedly, and who had met the responding physician prior to death were included (n = 2842). We examined three age groups: 65–79, 80–89, and 90+ years. Logistic regression analysis was used to identify age-related differences, controlled for place of death and sociodemographic characteristics. RESULTS In 83.8% of the study population at least one medical end-of-life decision was made, and for 39.4% the use of a potentially life-sustaining treatment was documented. Alleviation of pain and other symptoms with a possible life-shortening effect was performed with 29% higher odds among the 90+-year-olds (odds ratio [OR] 1.29, 95% confidence interval [CI] 1.01–1.66) than in the youngest age group. Withholding or withdrawing potentially life-sustaining treatment with or without the explicit intention to hasten death did not differ with age. However, when the frequency of withholding a potentially life-sustaining treatment was compared with the frequency of using this treatment (either continued until death or withdrawn later on), the former was more common in old age (80–89 years), and particularly in very old age (90+ years) for most of the treatments studied. This applied especially for ventilator therapy (80–89 years: OR 2.83, 95% CI 1.82–4.41; 90+ years: OR 6.17, 95% CI 2.89–13.17, compared with 65–79 years), artificial nutrition (ORs 2.33, 95% CI 1.46–3.71 and 4.44, 95% CI 2.28–8.65, respectively), and antibiotics (ORs 1.53, 95% CI 1.11–2.09 and 1.57, 95% CI 1.05–2.35, respectively). Age had no independent impact on artificial hydration. CONCLUSIONS The use of some potentially life-sustaining treatments decreased with older age and, in relation, the relative frequency of withholding such treatments increased. There may be various reasons for this finding: less benefit of a particular treatment in older patients for instance due to comorbidities, higher burden of treatment, and finally a tacit consensus of physicians and patients that death is nearing.